Back Cover: Stereocontrolled Synthesis of Chiral Heteroaromatic Propellers with Small Optical Bandgaps (Angew. Chem. Int. Ed. 15/2019). Issue 15 (5th March 2019) - Navakouski, Maksim; Zhylitskaya, Halina; Chmielewski, Piotr J.; Lis, Tadeusz; Cybińska, Joanna; Stępień, Marcin
Abstract : A simple reagent, N ‐bromosuccinimide, is the oxidant of choice in the stereospecific synthesis of azacoronene propellers. This new family of chiral chromophores features small electronic bandgaps, rich redox chemistry, and large chiroptical responses, as discussed by M. Stępień and co‐workers in their Communication onpage 4929.